(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The study reviews the situation of Algerian Indigenous people in the Oranian department before the First World War, 1908-1914, and their reactions to the application of the Conscription Law, 1912, including protests, delegations, petitions, complaints, uprisings, the Beni Chougrane Uprising of 1914, and migration to Arab and Islamic countries, including Syria, such as the 1911 Tlemcen migration. In light of the colonialist manoeuvres to exploit the youth for its military purposes, given that Algeria is a French colony, at a time when the general situation was characterized by deteriorating economic and social conditions and the persistence of repressive laws, including the law of the people, the elites of all spectrums played an important role in expressing the aspirations of Algerians expressing rejection and the desire for reforms in exchange for recruitment.